Evaluate the effectiveness of using non-pharmacological intervention during childbirth: an improvement project in Jordanian maternity hospitals - Lina Mrayan; Sanaa Abujilban; Ameera AbuKaraki; Abdulqadir J. Nashwan (BMC, 2024)
Abstract Background Unnecessary childbirth interventions are still common in most hospitals in Jordan. Despite the recommendations from the WHO that unnecessary interventions during childbirth should be avoided, these interventions are still used. Non-pharmacological pain management interventions are considered a convenient alternative to unnecessary childbirth interventions because they can prevent unsafe side effects for mothers during childbirth. The study aims to determine the feasibility of non-pharmacological pain management interventions during childbirth and then to evaluate their influence on mothers' experience. Methods Between May and June 2022, we implemented a quality improvement project with a bundle of non-pharmacologic comfort measures during childbirth. We started our project by (1) approaching all low-risk pregnant mothers who visited the hospital's antenatal clinic with a gestational age greater than 36 weeks. (2) Following the agreement, the researcher indicated that she would accompany the mother during the birthing process. (3) The researcher discussed different non-pharmacological pain management techniques and asked the mothers to choose how and when to utilize them. Non-pharmacological pain management techniques include breathing exercises, back massages, enabling mothers to move around, and providing modest amounts of water and soft food. (4) A few days after birth, the mother was interviewed one-to-one utilizing semi-structured audio-recorded interviews. The researcher interviewed eighteen postpartum mothers at a place of their choosing. Results Three main themes emerged from the interview analysis. The following themes were selected from the participants' own words: "Positive, respectful, and satisfying childbirth experience"; "Maintain mother's sense of control and cope with childbirth pain"; and "Birth outcome". These themes are connected and impacted by one another. Discussion Different research studies from diverse cultures recommend limiting the unnecessary use of interventions during childbirth and not interfering with childbirth unless medically necessary. Our participants expressed satisfaction with the use of culturally appropriate birth interventions during childbirth. These interventions were generally simple and safe, resulting in a satisfying birthing experience. Conclusion The study findings contribute to achieving Sustainable Development Goal #3, "Good health and well-being" by reducing maternal and neonatal mortality, providing evidence of the effectiveness of non-pharmacological pain management, and avoiding unnecessary childbirth interventions.